1973
DOI: 10.1111/j.1095-8649.1973.tb04478.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an in vivo method for monitoring ovarian development in the grey mullet (Mugil cephalus L.)

Abstract: The validity of using extruded intra-ovarian oocytes for in vivo assessment of ovarian maturity in the grey mullet was established. The diameter of sampled, unfixed oocytes was used as a reference point for comparative purposes. Analysis of variations in oocyte diameters among samples removed from seven different ovarian locations indicated that mullet oocytes develop in synchrony and that in vivo samples taken from any area in the ovary would be representative of the entire ovary. Statistical analyses of oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 1 publication
1
37
0
1
Order By: Relevance
“…The preservative solution did not affect the oocyte diameters within 24 h. The same was observed in other species (Shehadeh et al, 1973;AlvarezLajonchère et al, 1983AlvarezLajonchère et al, , 2001Tamaru et al, 1988), although Garcia (1989-a) reported an increase in L. calcarifer oocyte diameters after one hour in a buffered 5% formalin solution. Ovarian biopsy methods have been validated on synchronous as well as asynchronous oocytedevelopment species (Shehadeh et al, 1973, Markmann andDoroshov, 1983;AlvarezLajonchère et al, 1983AlvarezLajonchère et al, , 2001Rodriguez and Garzo, 1986).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The preservative solution did not affect the oocyte diameters within 24 h. The same was observed in other species (Shehadeh et al, 1973;AlvarezLajonchère et al, 1983AlvarezLajonchère et al, , 2001Tamaru et al, 1988), although Garcia (1989-a) reported an increase in L. calcarifer oocyte diameters after one hour in a buffered 5% formalin solution. Ovarian biopsy methods have been validated on synchronous as well as asynchronous oocytedevelopment species (Shehadeh et al, 1973, Markmann andDoroshov, 1983;AlvarezLajonchère et al, 1983AlvarezLajonchère et al, , 2001Rodriguez and Garzo, 1986).…”
Section: Discussionmentioning
confidence: 57%
“…The biopsies were taken during the morning (09.00-10.00 hours) from females anesthetized with benzocaine (50 ppm), using a 0.8-mm diameter polyethylene cannula inserted through the oviduct to approximately the central portion of one of the ovaries. The intra-ovarian oocyte samples were drawn by suctioning while the cannula was slowly withdrawn and then either measured immediately or preserved in 10-mL vials with a solution of 1% formalin in 0.9% NaCl (Shehadeh et al, 1973). The oocytes were examined on a 60 mm-diameter Petri dish, under stereomicroscope and their diameter individually measured with an ocular micrometer to the smallest division, which measured 25 µm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature females of thin-lipped grey mullet were selected on the basis of the presence of a soft, swollen abdomen and protruding genital papillae. The maturity and the oocyte diameters of the females were staged by obtaining in vivo biopsy of the ovary using a polyethylene cannula [34] . The females that were used possessed oocytes whose diameters were greater than 600 µm.…”
Section: Seawater Acclimation and Induction Of Spawningmentioning
confidence: 99%
“…Most effort has been directed at Mugil cephalus, particularly with regard to induced spawning (Pien & Liao 1975;Kuo, Nash & Shehadeh 1974;Shehadeh, Kuo & Milisen 1973). Histological investigations have been carried out by Stenger (1959), Abraham (1963), Abraham, Blanc & Yashouv (1966), and Zhitenev, Kalinen & Abayev (1974).…”
Section: Department Of Zoology University Of Port Elizabethmentioning
confidence: 99%